Diseño de indumentaria urbana a partir del análisis del vestuario de los personajes de la serie anime One Piece” - Guerrero Santillán, Arianna Giselle (2024)
This proposal was aimed to analyze the costumes of characters from the anime series One Piece, particularly the main characters, to design urban clothing. To understand the relevant aspects, focus groups were conducted with university students aged 22 to 28 who are fans and connoisseurs of the series. Following this, an observation sheet was utilized with the interviewed group and a character sheet was created, containing information about the personality and costumes of each character. The data obtained served as a foundation for developing proposals and sketches for urban clothing that the target group could identify with and feel comfortable wearing. Consumer preferences regarding silhouettes, clothing, colors, and other aspects were considered, incorporating representative elements of the characters through the abstraction of shapes, silhouettes, and other features. This ensured that these components were easily recognizable by young fans of One Piece within the community. In conclusion, this project successfully addressed the desires and needs of the target group for urban clothing inspired by their favorite anime series. The integration of representative elements into each garment resulted in innovation within the market and satisfaction among the users.